Ice‐Marginal Proglacial Lakes Across Greenland: Present Status and a Possible Future. Issue 12 (15th June 2022) - Carrivick, Jonathan L.; How, Penelope; Lea, James M.; Sutherland, Jenna L.; Grimes, Michael; Tweed, Fiona S.; Cornford, Stephen; Quincey, Duncan J.; Mallalieu, Joseph
Abstract: Ice‐marginal lakes can affect glacier dynamics but are ignored in studies of the evolution of the Greenland ice sheet (GrIS) and of peripheral mountain glaciers and ice caps (PGICs). Here we show that lakes occupy 10% of the GrIS ice margin and occur on 5% of PGICs. Ice velocity at the GrIS margin is enhanced by ∼ 25% at lakes versus on land. Mean ice discharge into lakes is ∼4.9 Gt.yr, which is ∼1% of ice discharged through marine termini. We locate thousands of subglacial overdeepenings within which 7, 404 km 2 of future lakes could form, all of which will be ice‐marginal at some time. Future lakes in the west and east will be restricted to the margin of the GrIS and within alpine valleys, respectively. This status and possible future leads us to contend that lakes should be incorporated into projections of Greenland ice loss. Plain Language Summary: Lakes forming on the edges of glaciers can affect ice dynamics but are not included within numerical models of the Greenland ice sheet (GrIS) or of peripheral mountain glaciers and ice caps (PGICs). We show that lakes presently occupy 10% of the GrIS ice margin and occur on 5% of PGICs. We determine that ice is typically moving 25% faster in the vicinity of lakes than at land margins. We estimate that ice discharge into lakes is ∼4.9 Gt.yr, which is 1% of that through marine glaciers. We identify thousands of depressions in the landscape that could hold future lakes as glaciers retreat from them. Overall, understanding of lake evolution should be incorporated into projections of Greenland ice loss and runoff. Key Points: Lakes occupy 10% of the ice margin and vary between 2% and 26% by region Ice velocity is ∼25% greater into lakes compared to onto land and total ice discharge into lakes is ∼4.9 Gt.yr −1 Thousands of overdeepenings have potential to host more and larger lakes in the future but not all will be ice‐marginal simultaneously